2014
DOI: 10.1530/erc-13-0485
|View full text |Cite
|
Sign up to set email alerts
|

VGLL1 expression is associated with a triple-negative basal-like phenotype in breast cancer

Abstract: Vestigial-like 1 (VGLL1) is a poorly characterized gene encoding a transcriptional co-activator structurally homologous to TAZ and YAP that modulates the Hippo pathway in Drosophila. In this study, we examined the expression of VGLL1 and its intronic miRNA, miR-934, in breast cancer. VGLL1 and miR-934 expression miRNA profiling was carried out on frozen samples of grade 3 invasive ductal carcinomas. VGLL1 protein was also examined in 433 sporadic and BRCA1-associated breast carcinomas on tissue microarrays. RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 38 publications
3
50
1
Order By: Relevance
“…Therefore, the identification of specific biomarkers/molecular targets is imperative. In this regard, we have recently reported that Vgll1, a transcriptional cofactor with structural similarities to TAZ and YAP1, is mainly expressed in a subset of sporadic and BRCA1-associated TN/basal breast carcinomas (Castilla et al 2014). In a recent report by Bartucci et al (2014), TAZ IHC expression in a cohort of 99 tumors was not significantly correlated with receptor status, although the authors did observe an association between high tumor grade and Ki67 index, as we have observed in the present study.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Therefore, the identification of specific biomarkers/molecular targets is imperative. In this regard, we have recently reported that Vgll1, a transcriptional cofactor with structural similarities to TAZ and YAP1, is mainly expressed in a subset of sporadic and BRCA1-associated TN/basal breast carcinomas (Castilla et al 2014). In a recent report by Bartucci et al (2014), TAZ IHC expression in a cohort of 99 tumors was not significantly correlated with receptor status, although the authors did observe an association between high tumor grade and Ki67 index, as we have observed in the present study.…”
Section: Discussioncontrasting
confidence: 50%
“…A series of 640 formalin-fixed paraffin-embedded (FFPE) human invasive breast carcinomas, including some cases from a previous study (Castilla et al 2014) and an independent tumor set of 15 metaplastic breast carcinomas (MBC), were obtained from the archives of the Department of Pathology of the Hospital Universitario Virgen del Rocío, Sevilla, Spain. The tumors had been diagnosed between 2007 and 2011, and the only selection criteria were the availability of pathological data and tissue for tissue microarray (TMA) construction.…”
Section: Human Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The miR-934 was the most strongly up-regulated microRNA in triple-negative IDCs (61.5-fold increase with respect to ER+ breast carcinomas) 32. Although studies about hsa-miR-3196 are rare, it was found that miR-3196 was down-regulated in basal cell carcinoma compared with nonlesional skin 33, and was also down-regulated in PTC patients with non-(131) I-avid lung metastases versus (131)I-avid lung metastases 34.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, several other keratins (e.g., KRT14, KRT15) are included to construct the gene interaction network. VGLL1 (Vestigial-like 1) is a gene encoding a transcriptional co-activator modulating the Hippo pathway, which is known to be associated with a basal-like phenotype in breast cancer36. Participation of FZD9 in carcinogenesis has been reported in various cancers, indicating their potential roles in breast cancer, such as mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%